Article Commentary: The Arts and Family Business: Linking Family Business Resources and Performance to Industry Characteristics. (November 2015) - Le Breton–Miller, Isabelle; Miller, Danny
There has been a good deal of debate regarding the performance of family firms. Explanations for divergent findings have ranged from variations in governance arrangements to particular organizational practices. One avenue that has not been much explored is the role played by industry. We theorize that market requirements, when coupled with firm–specific behaviors and resources, can account for why some family businesses do well in particular industries. More precisely, due to their long–term orientation and the intimate connection among family members, some family firms are especially adept at accumulating human capital, passing on tacit knowledge, protecting and leveraging reputation, and building strong relationships and slack resources. These capacities promote success in industries with high levels of uncertainty regarding product quality, product value, and demand. The arts–related industries, we shall argue, are one such environment, and we use it to demonstrate our thesis that family firms, if oriented appropriately, can thrive where relationships, tacit knowledge, and reputation are demanded.